Создание электронных лекций - Бондарев, В. М. (УАДО, 2002)
The easy way to produce the computer lectures is proposed. Lecturer can create them without special knowledge in area of computing or web technology. The approach is based on the tag library concept.
Keywords: электронная лекция; дистанционное обучение